"ДЕКЛАРАЦИЯ ОБ УСТАНОВЛЕНИИ НОВОГО МЕЖДУНАРОДНОГО ЭКОНОМИЧЕСКОГО ПОРЯДКА"[1] И СУВЕРЕНИТЕТ НАД ПРИРОДНЫМИ РЕСУРСАМИ (Journal of actual problems of jurisprudence, 2019)
The article deals with the meaning and importance of the declaration on the new economic order.